Pengaruh Latihan ROM (Range of Motion) Pasif Terhadap Peningkatan Kemampuan Motorik Pada Pasien CVA Infark Di Ruang Pajajaran RSUD Prof.Dr.Soekandar Mojosari Mojokerto - Nur So’emah, Eka (JURNAL KEPERAWATAN BINA SEHAT, 2014)
A CVA Infark can cause defects in the form of paralysis, impaired mobility and how to minimize disability after CVA Infark is in rehabilitation with exercise is the motion of joints or passive ROM. This research aims to identify the influences of passive ROM exercises to increase the ability of motor on CVA Infark patients in Pajajaran RSUD Prof.Dr.Soekandar Mojosari. The design used in this research are pre-method of one group pretest – posttest. As the population in ischemic stroke patients is the Pav.Pajajaran RSUD Prof.Dr.Soekandar Mojosari. A sample of 15 people selected by non-probability sampling methods with consecutive sampling. Instrument research using Manual Muscle Testing. Data analysed using the T-test of paired samples. Results before being given a passive ROM exercises on average had one muscle strength scale, after being given an average exercise improved muscle strength. T-test analysis Test shows that there is the influence of exercise on the ROM upgrade on motor pre and post test (ρ=0,000< 0.05). The implications of this research are passive ROM exercises can improve motor ability ekstermitas in CVA Infakr patients. Necessitating the granting of passive ROM exercises as early as possible.